Cyprus Statistical Society - (:unkn) unknown (My University, 2026)
The Cyprus Statistical Society (C.S.S.) is a scientific association based in Nicosia that was founded in 2018. The purpose of C.S.S. is the promotion and dissemination of all branches of Statistical Science, both its theory and its applications, as well as the recognition of the contribution of Statistical Science to other sciences and to important areas of human activity. It also aims to consolidate the prestige of the profession of Statistics and to promote the teaching of Statistics at all levels of education. The goals of C.S.S. are achieved through actions such as the organization of lectures, conferences and competitions and the publication of scientific journals. At the same time, the C.S.S. will seek the maximum degree of cooperation with corresponding scientific organizations of other countries. The C.S.S. is a founding member of the Federation of European National Statistical Societies (FenSTATs) of which he is a member since 2018.